Analysis of Precipitates from Acetone Extracts of Feronia limonia - Ulagi, R.; Pitchai, P.; Mohan, P.S.; Gengan, R.M. (Asian Journal of Chemistry, 2011)
Vitexin and sucrose were isolated from acetone extracts of air-dried flowers of Feronia limonia. Their structures were elucidated by spectral studies and comparison with literature data.